Radiographers' experiences and perspectives of forensic imaging in Australia: A qualitative study. Issue 4 (November 2022) - Smith, B.; Makanjee, C.R.; Lee, H.; Hayre, C.M.; Lewis, S.
Abstract: Introduction: Forensic imaging plays a pivotal role regarding medico-legal issues by investigating the cause(s) of injuries to living or deceased individuals. There is currently a gap in the literature on forensic imaging due to limited national and international guidelines, protocols and scope of duties and responsibilities of radiographers undertaking forensic imaging. Thus, this study aimed to investigate the gap by exploring the experiences and perspectives of radiographers on forensic imaging in Australia. Methods: A qualitative approach collected data from fifteen purposively sampled qualified Australian radiographers through individual in-depth interviews. The verbatim transcribed data were thematically analysed. Results: Two themes were identified: 1) Radiographers' experiences of forensic imaging; 2) Radiographers' perceptions of forensic imaging within the job scope of a qualified radiographer. Conclusions: Participants' experiences of forensic imaging ranged from anxiety to a positive experience, and others posed ethical and situational dilemmas heightened by the lack of dedicated forensic imaging protocols. While some radiographers expressed that every radiographer should conduct forensic imaging, others felt it was not mandatory. Implications for practice: Radiographers' shared subjective experiences, thoughts and feelings provided insight into forensic imaging and the need for more significant support from educational and governing bodies.